2018
DOI: 10.2147/ce.s118670
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine for the treatment of advanced or metastatic transitional cell carcinoma of the urothelial tract: an evidence-based review of safety, efficacy, and place in therapy

Abstract: BackgroundA systematic review and meta-analysis of the use of systemic vinflunine (VIN) in the treatment of urothelial carcinoma (UC) was performed to evaluate its efficacy based on current available clinical data.MethodsThis review was prospectively registered at the International Prospective Register of Systematic Reviews, PROSPERO (registration CRD42016049294). Electronic databases including MEDLINE®, Embase®, Cochrane Central Register of Controlled Trials, and Web of Science were searched through December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This response rate exceeds the numbers reported for other chemotherapy regimens in unfit patients, e.g. the phase III trial CG vs M-CAVI [5] (including the subgroup treated with CG unfit to cisplatin only due to impaired renal function, ORR 47%, CR 6%), the JASINT1 trial [16] and vinflunine in second-line treatment [14,15]. The response rate in our trial is comparable with the best response data reported for cisplatin-based chemotherapy in aUC [3,21,22].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This response rate exceeds the numbers reported for other chemotherapy regimens in unfit patients, e.g. the phase III trial CG vs M-CAVI [5] (including the subgroup treated with CG unfit to cisplatin only due to impaired renal function, ORR 47%, CR 6%), the JASINT1 trial [16] and vinflunine in second-line treatment [14,15]. The response rate in our trial is comparable with the best response data reported for cisplatin-based chemotherapy in aUC [3,21,22].…”
Section: Discussionsupporting
confidence: 67%
“…In 2009, the European Medicines Agency (EMA) approved the third-generation anti-microtubule inhibitor vinflunine as second-line treatment after platinum-based chemotherapy in patients with aUC, improving mOS for vinflunine compared with best supportive care in the eligible population (but not in the intention-to-treat [ITT] population) [14]. Furthermore, the efficacy of vinflunine in second-line treatment has been confirmed in real-world studies [15]. Vinflunine combinations, vinflunine and gemcitabine (VG) versus vinflunine and carboplatin, were explored as first-line treatment for cisplatin-unfit patients in the randomised phase II trial JASINT1 [16], showing promising response rates and survival (ORR 53% with confirmed ORR 44% and mOS 14.0 months in the VG arm), although the trial did not include a non-investigational control arm.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a critical review of these publications is necessary to extract useful information and reliable conclusions on the everyday utilization of VFL. Recently, a meta-analysis including RWD on VFL in mUC was published [36], however, this meta-analysis also included all published phase II and III clinical trials of VFL, thus neutralizing the important advantages of a pure RWD analysis. We therefore conducted a meta-analysis completely focused on RWD on VFL.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors: ECOG PS  1, liver metastases, Hb 10 g/dL[34]. ‡ Risk factors: ECOG PS  1, liver metastases, Hb 10 g/dL, time-from-prior-chemotherapy <6 months[36].…”
mentioning
confidence: 99%
“…In line with the in vitro culture results, the in vivo xenograft model clearly supported the hypothesis that TSA works synergistically with paclitaxel. Although the cooperative antitumor effect between TSA and paclitaxel was observed in papillary serous endometrial cancer cells [ 32 ], whether the synergistic effect holds for other cancer types, especially those that exhibit drug resistance, is unclear. Our study results indicate that the synergistic antitumor effect is well preserved in high-grade UC cells despite their insensitivity to other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%